Awareness and Acceptance of Telehealth among Filipinos in the National Capital Region+ - Dalisay, Ricky; Pelaez, Trisha Claire; Dimaculangan, Ernesto (IJOSMAS, 2022)
Telehealth has gained interest as the rise of the COVID-19 pandemic threatened the safety of every individual, causing the services' expansion worldwide to minimize the spread of the virus. This study explored Filipinos' awareness, perceptions, and acceptance of Telehealth services and examined the correlation between the variables. Quantitative research design with Descriptive Statistics, Pearson R Correlation, and Multiple Regression were utilized to analyze the data gathered from an online survey questionnaire via Google Forms administered to three hundred eighty-five (385) respondents residing in the National Capital Region+ of the Philippines. Results showed that Filipinos agree about being aware of Telehealth services. The subjects also indicated agreement about having positive usefulness and accessibility perceptions about the service, as well as their agreement to accept Telehealth services. Moreover, results showed a significant positive relationship between awareness and the usefulness and accessibility perceptions of Telehealth. The same is true between the usefulness and accessibility perceptions and acceptance of the service. In conclusion, the research results affirm the awareness, perceptions, and acceptance of Filipinos regarding Telehealth services and highlighted the importance of promoting the usefulness and accessibility of Telehealth services since the two perception variables ultimately affect consumers' acceptance to use the service.